The complete HTML and CSS course (Manning Publications, 2021)
All new web developers must learn the basics of HTML and CSS, as they’re the languages used to build and style a website. This course shows you how to code in HTML and CSS from the ground up, from the absolute fundamentals to the advanced topics. Whether you are a beginner learning from scratch or an experienced coder looking to brush up on specific areas, you will find something new and useful in this course. You’ll begin by learning the components of HTML, including its lists, tables, URLs, hyperlinks, iframing, and many other important aspects of the language. As you understand the individual components, you’ll also learn how to put all of them together to create a structure for your website to style with CSS. Then, you’ll meet and work with the fundamentals of CSS, such as selectors, dimensions, box models, lists, texts, fonts, tables, and other essentials. With basic knowledge of both languages, you can confidently style the HTML structures you created earlier to make fully-fledged websites. With web developers making up to $140,000 annually, a course in HTML and CSS might be the most rewarding thing you'll do this year. After the course, we'll share tips on the next languages to learn in order to carve out a career in frontend website development.